2019
DOI: 10.1111/medu.13811
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐role mentoring: mentors’ conceptualisations, enactments and role conflicts

Abstract: Introduction Outcome‐based approaches to education and the inherent emphasis on programmatic assessment in particular, require models of mentoring in which mentors fulfil dual roles: coach and assessor. Fulfilling multiple roles could result in role confusion or even role conflicts, both of which may affect mentoring processes and outcomes. In this study, we explored how mentors conceptualise and enact their role in a multiple‐role mentoring system and to what extent they experience role conflicts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
5
39
0
1
Order By: Relevance
“…Although for some teachers the dual purpose of low‐stake assessment may continue to represent an unhappy marriage, our results showed that a role conflict is not necessary. Similar findings emerged in a study on multiple‐role mentoring in programmatic assessment . Conflicts in our study were reported only in relation to struggling and underperforming learners.…”
Section: Discussionsupporting
confidence: 90%
“…Although for some teachers the dual purpose of low‐stake assessment may continue to represent an unhappy marriage, our results showed that a role conflict is not necessary. Similar findings emerged in a study on multiple‐role mentoring in programmatic assessment . Conflicts in our study were reported only in relation to struggling and underperforming learners.…”
Section: Discussionsupporting
confidence: 90%
“…Fourteen studies reported that programmatic assessment generated sufficient information to enable meaningful triangulation and high-stakes, robust decision-making [15,16,18,19,24,25,[29][30][31][32][37][38][39][40]. Arguments for this conclusion involved findings such as high levels of assessors' agreement [24,30,32,37]; the perceived fairness or acceptability by learners and teachers [23,24,30]; satisfactory reliability estimates [15, 23-25, 29, 31, 37]; the coherent nature of the program that ensured all competencies were considered [17, 18, 21, 22, 28-30, 34, 38]; and early detection of struggling learners [15,18,22,24,32,38], specifically of problematic progression on the domains of professionalism and communication, which went undetected prior to implementation [15,24].…”
Section: Theme 1: the Integration Of The Decision-making And Learningmentioning
confidence: 99%
“…The recent trend towards programmatic assessment in medical education offers an example of the dynamic nature of our field and reminds us of the challenges and opportunities that arise when trying to make sense of well-established concepts in ever-changing contexts. In this issue, Meeuwissen et al 3 describe mentors' experiences in the context of a change in curriculum from one that prioritised 'assessment of learning' to one designed to enable 'assessment for learning'. 4,5 After the transition, some mentors experienced role conflicts between the different paradigms of nurturing and assessment.…”
mentioning
confidence: 99%
“…The question, therefore, of how mentoring can be practised and shaped to enable programmatic assessment is not sufficient. As Meeuwissen et al 3 imply, mentoring in programmatic assessment may need to evolve as mentoring becomes a practice in its own right, but, just as in clinical work, practice entails judicious fulfilment of different needs for different individuals. The consideration of a single fixed model of mentoring, developed within a certain population, does nothing to guarantee the successful use of programmatic assessment.…”
mentioning
confidence: 99%